Strong invaders are strong defenders – implications for the resistance of invaded communities. (7th March 2016) - Henriksson, Anna; Wardle, David A.; Trygg, Johan; Diehl, Sebastian; Englund, Göran
Abstract: Many ecosystems receive a steady stream of non‐native species. How biotic resistance develops over time in these ecosystems will depend on how established invaders contribute to subsequent resistance. If invasion success and defence capacity (i.e. contribution to resistance) are correlated, then community resistance should increase as species accumulate. If successful invaders also cause most impact (through replacing native species with low defence capacity) then the effect will be even stronger. If successful invaders instead have weak defence capacity or even facilitative attributes, then resistance should decrease with time, as proposed by the invasional meltdown hypothesis. We analysed 1157 introductions of freshwater fish in Swedish lakes and found that species' invasion success was positively correlated with their defence capacity and impact, suggesting that these communities will develop stronger resistance over time. These insights can be used to identify scenarios where invading species are expected to cause large impact.